Isolation and Screening of Molds from Traditional Look-pang Starter Cultures for Rice Syrup Production - Prommajak, Trakul; Chanchomsuk, Chanthana; Chailangka, Kamonlak; Srimuang, Kanok-orn; Attabhanyo, Ratana (Food and Applied Bioscience Journal, 2024)
Rice syrup can be produced naturally by fermenting cooked rice with microorganisms derived from traditional starter cultures. In this study, we focused on identifying and assessing the sugar production of fungi present in Look-pang, a traditional starter. We employed both submerged fermentation in starch broth and solid-state fermentation techniques on cooked rice to isolate fungal strains from Look-pang. Of these, Aspergillus tamarii stood out for its superior sugar production. The reducing sugar and glucose concentrations achieved from solid-state fermentation using this culture were in line with findings from previous studies. Notably, A. tamarii is known to produce both beneficial health compounds and potential toxins under specific conditions. The significant role of A. tamarii in the fermentation dynamics of Look-pang underscores its potential in advancing organic rice syrup production, representing a step forward in sustainable food processing.